Executive function and bilingualism in young and older adults - Kousaie, Shanna; Sheppard, Christine; Lemieux, Maude; Monetta, Laura; Taler, Vanessa (Frontiers in Behavioral Neuroscience, 2014)
Research suggests that being bilingual results in advantages on executive control processes and disadvantages on language tasks relative to monolinguals. Furthermore, the executive function advantage is thought to be larger in older than younger adults, suggesting that bilingualism may buffer against age-related changes in executive function. However, there are potential confounds in some of the previous research, as well as inconsistencies in the literature. The goal of the current investigation was to examine the presence of a bilingual advantage in executive control and a bilingual disadvantage on language tasks in the same sample of young and older monolingual anglophones, monolingual francophones, and French/English bilinguals. Participants completed a series of executive function tasks, including a Stroop task, a Simon task, a sustained attention to response task (SART), the Wisconsin Card Sort Test (WCST), and the digit span subtest of the Wechsler Adult Intelligence Scale, and language tasks, including the Boston Naming Test (BNT), and category and letter fluency. The results do not demonstrate an unequivocal advantage for bilinguals on executive function tasks and raise questions about the reliability, robustness and/or specificity of previous findings. The results also did not demonstrate a disadvantage for bilinguals on language tasks. Rather, they suggest that there may be an influence of the language environment. It is concluded that additional research is required to fully characterize any language group differences in both executive function and language tasks.